Masstige Positioning for Music Streaming Services and the Role of Consumer Ethnocentrism - Pramit Yadav, Dr. Preetha Menon (International Journal of Advanced Science and Technology, 2020)
With the increasing acceptability of paid content streaming applications and the lack of strong differentiation in the offerings of the competing music streaming services, brands are looking for an optimal positioning. Both global and domestic players in the music streaming market face the challenge of converting free users to paid subscribers. To this affect, this paper evaluates the masstige (mass-prestige) quotient of the competing brands while also understanding the role of consumer ethnocentrism in the purchase decision of digital streaming services. Our study finds that both global and domestic music streaming apps are currently not perceived to be masstige but show potential to achieve this positioning in the long term. The research further shows a statistically significant influence of consumer ethnocentrism and consumer age on their perceptions towards global vs domestic apps. Based on these considerations, the paper further outlines the marketing opportunities available for a potential masstige positioning of the music streaming services in India.